Risks of clothing manufacturing enterprises in Kazakhstan: analysis and ways to reduce - Yepanchintseva, S.E.; Ashimova, Zh.R.; Momynkulova, S.M. (BUKETOV BUSINESS REVIEW, 2024)
Object: To investigate the risks of clothing manufacturing enterprises in Kazakhstan in modern conditions, to identify ways to reduce them. Methods: The research is based on the methods of system analysis, comparative analysis, synthesis, review of scientific and journalistic literature, systematic and dialectical-logical approach. Results: The authors of the article identify the main features of the functioning of clothing manufacturing enter prises, their specifics in modern conditions. Based on the conducted research, the key risks of the industry enterprises were identified, their classification was carried out with the allocation of foreign economic, industrial, commercial, financial, social, legal and personnel risks. The characteristics of the identified risks are given and an assessment of the possible consequences of the implementation of these risks is carried out. The analysis identifies the key problems of clothing manufacturing enterprises, which are the main sources of entrepreneurial risks. Conclusions: The risks associated with increased competition, which is a consequence of integration processes in the world, are identified as the most significant risks for clothing manufacturing enterprises. According to the results of the study, the authors identified the main ways to reduce risks and promote Kazakhstan products to foreign and domestic markets. A set of measures that are aimed at risk management at clothing manufacturing enterprises should include actions to reduce general and specific risks. According to the authors, the creation of strategic partnerships and alliances in the production of clothing in Kazakhstan should become the leading direction for reducing risks and promoting domestic products to world markets.